2018
DOI: 10.1002/cam4.1758
|View full text |Cite|
|
Sign up to set email alerts
|

TGF‐β‐mediated exosomal lnc‐MMP2‐2 regulates migration and invasion of lung cancer cells to the vasculature by promoting MMP2 expression

Abstract: Previous studies indicated that transforming growth factor (TGF)‐β‐mediated exosomal microRNAs (miRNAs) regulate the migration and invasion of lung cancer cells; however, whether and how TGF‐β‐mediated exosomal long noncoding (lnc) RNAs regulate migration and invasion of lung cancer cells remains unclear. Here, coculture experiments showed that TGF‐β pretreatment increased the migration and invasion potential of lung cancer cells and TGF‐β pretreated A549 cells increases vascular permeability. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 29 publications
0
78
0
Order By: Relevance
“…Several signaling pathways can regulate cancer cell proliferation, migration, and invasion, however, it is unclear which one is directly involved in this phenomenon. In light of significance of TGFβ1, SHH, EGFR, and LEF‐1 in the proliferation and migration of cancer cells, we examined the differential expression of those proteins in the cell lysis solution of NFs and CAFs and paid our attention to the different expression of SHH. As previously reported, abnormal activation of Hedgehog signaling pathway was positively correlated with the clinical manifestations, lymph node metastasis, and overall survival rate of many cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways can regulate cancer cell proliferation, migration, and invasion, however, it is unclear which one is directly involved in this phenomenon. In light of significance of TGFβ1, SHH, EGFR, and LEF‐1 in the proliferation and migration of cancer cells, we examined the differential expression of those proteins in the cell lysis solution of NFs and CAFs and paid our attention to the different expression of SHH. As previously reported, abnormal activation of Hedgehog signaling pathway was positively correlated with the clinical manifestations, lymph node metastasis, and overall survival rate of many cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, mobilization of exosomes is regulated by TGF-β. For example, TGF-β is involved in the transport of MMP2 containing exosomes in malignancy disorders [168]. Therefore, it can be speculated that the increased levels of TGF-β in brains with AD and VaD may play a key role in transport and accumulation of amyloid-β responsible for neurodegeneration.…”
Section: Role Of Tgf-β On Exosomes and Microvesicles In Vadmentioning
confidence: 99%
“…LncRNA H19, shuttled from CD90 + liver cancer cells to endothelial cells, promotes its tube formation and cell‐cell adhesive properties by enhancing the expression of VEGF and ICAM‐1, respectively 48 . In lung cancer, sEV lncMMP‐2‐2 upregulates vascular endothelial cell permeability upon TGF‐β stimulation 49 . It has also been reported that sEV lncRNA CCAT2 and lncRNA POU3F3 derived from glioma cells enhance endothelial cell migration, proliferation, tube formation in vitro and arteriole formation in vivo 50,51 .…”
Section: Extracellular Vesicle Long Non–coding Rna Mediate Crosstalkmentioning
confidence: 99%